Stereotactic radiofrequency ablation of a variety of liver masses in children. (1st January 2020) - Hetzer, Benjamin; Vogel, Georg-Friedrich; Entenmann, Andreas; Heil, Michel; Schullian, Peter; Putzer, Daniel; Meister, Bernhard; Crazzolara, Roman; Kropshofer, Gabriele; Salvador, Christina; Straub, Simon; Karall, Daniela; et al.
Abstract: Background and aims: Surgical resection is currently the cornerstone of liver tumor treatment in children. In adults radiofrequency ablation (RFA) is an established minimally invasive treatment option for small focal liver tumors. Multiprobe stereotactic RFA (SRFA) with intraoperative image fusion to confirm ablation margins allows treatment for large lesions. We describe our experience with SRFA in children with liver masses. Methods: SRFA was performed in 10 patients with a median age of 14 years (range 0.5–17.0 years) suffering from liver adenoma ( n = 3), hepatocellular carcinoma ( n = 1), hepatoblastoma ( n = 2), myofibroblastic tumor ( n = 1), hepatic metastases of extrahepatic tumors ( n = 2) and infiltrative hepatic cysts associated with alveolar echinococcosis ( n = 1). Overall, 15 lesions with a mean lesion size of 2.6 cm (range 0.7–9.5 cm) were treated in 11 sessions. Results: The technical success rate was 100%, as was the survival rate. No transient adverse effects higher than grade II (Clavien and Dindo) were encountered after interventions. The median hospital stay was 5 d (range 2–33 d). In two patients who subsequently underwent transplant hepatectomy complete ablation was histologically confirmed. Follow-up imaging studies (median 55 months, range 18–129 months) revealed no local or distant recurrence of disease in any patient. Conclusions: SRFA is an effective minimal-invasive treatment option in pediatric patients with liver tumors of different etiologies.